Multiculturalism in Asia - Kymlicka, Will.; He, Baogang, 1957- (Oxford : Oxford University Press, 2005)
Exploring the different ways that ethnic and religious diversity is conceptualized and debated in south and east Asia, this text analyses the practical and theoretical challenges which need to be addressed in order to broaden the scope of the multicultural society in the region.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Multiculturalism -- Asia